Effectiveness of Sexual Imagery in Advertisements and Influence on Purchasing Behaviour of Consumers in Mumbai : A Study Across Genders and Generations - John, Jackson; D'Abreo, Jennifer (Indian Journal of Marketing, 2017)
In today's world of advertising and consumerism, use of sexual imagery is no longer considered a taboo, a trend fast catching-up in India too. The present study focused on understanding the effectiveness of use of sexual imagery in advertisements and how it influences consumer purchase intention. The study was conducted across genders and generations to examine variations, if any, in the results of the research. A brief introduction to the concept of sexual advertising is presented along with a review of existing literature in the area. The study used both primary and secondary sources of data. Primary data were obtained from a survey conducted with 460 respondents across genders and generations in Greater Mumbai Metropolitan Region using a structured questionnaire. Data analysis was done by using correlation and simple linear regression methods. The results suggested that the use of sexual imagery had a positive influence on consumer purchase decisions, irrespective of gender or generation. This could imply that the use of sexual imagery by advertisers is a popular as well as successful strategy in grabbing audience's attention and affects their decision-making process, thereby inducing them to purchase the advertised product.